Congestion and Emissions Reduction in Freeway Traffic Networks via Supervisory Event-triggered Control. Issue 1 (July 2017) - Ferrara, A.; Pasquale, C.; Sacone, S.; Siri, S.
Abstract: This paper proposes an innovative control scheme for regulating traffic in freeway networks via ramp metering in order to reduce congestion and traffic emissions. The control scheme is composed by a supervisor, acting at a higher level, which receives measurements from the whole network and periodically makes a prediction on the system evolution, and by local feedback controllers, acting at a lower level. These latter are extended PI-ALINEA controllers which compute the control action not only on the basis of measurements immediately downstream the on-ramp, as in standard PI-ALINEA, but also on the basis of other measurements or predictions referred to farther locations which are time-varying and communicated by the supervisor. The supervisor decides when the control law of extended PI-ALINEA controllers needs to be changed according to an event-triggered logic.